2011
DOI: 10.1021/jp203155z
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Improve Crystallinity of Supported Nanoparticles Using Low Melting Point Metals

Abstract: The crystallinity of nanoparticles plays a crucial role in controlling materials’ mechanical, catalytic, magnetic and electronic properties. A novel method to improve the crystallinity of nanoparticles by doping and releasing of low melting point amalgamating metals was proposed and tested. The HRTEM micrographs of AgMC, Hg-doped AgMC, and Hg-released AgMC exhibited a significant improvement in crystallinity of silver nanoparticles supported on chabazite by a mercury adsorption–desorption cycle. Molecular dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…The formation of nanoalloys was supported by EDX analysis, XRD study, and an increase in the size of the nanoparticles suggested by the TEM analysis. The increment in size was due to the well-known “swelling effect”, 33 which occurs due to the diffusion of Hg atoms, which increases the total atoms per nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of nanoalloys was supported by EDX analysis, XRD study, and an increase in the size of the nanoparticles suggested by the TEM analysis. The increment in size was due to the well-known “swelling effect”, 33 which occurs due to the diffusion of Hg atoms, which increases the total atoms per nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] To this end, it is of critical importance to have an ability to manipulate the crystallinity of noblemetal nanocrystals. [15][16][17][18] Although noble-metal nanocrystals with different degrees of crystallinity may co-exist in the final products of a typical synthesis, it should be pointed out that the evolution of twin defects from single-crystal seeds during the growth may not be favored by thermodynamics. This is because the presence of defects will break the intrinsic cubic symmetry of the lattice and thus increase the total free energy of the system.…”
Section: Introductionmentioning
confidence: 99%
“…We interpret that the Ga-amide precursor undergoes thermolysis (Fig. 2, B and C), leading to the accumulation of liquid Ga on the NC surface without epitaxial constraints (35)(36)(37). Quick doping kinetics can be attributed to the fast thermolysis of the Ga-amide precursor and the large diffusion coefficient of liquid Ga (38), combined with the fact that Ga-doped Ag is a solid solution within the face-centered cubic (fcc) Ag phase.…”
Section: Amalgamation Mechanismmentioning
confidence: 91%